WAKAF PRODUKTIF DALAM PERSPEKTIF IMAM MADHAB - Dul Manan (Jurnal Mahkamah : Kajian Ilmu Hukum Dan Hukum Islam, 2016)
Text endowments that is have not yet been widely touch on comprehension contextual. Should endowments is one of the of various activities in economic system islamic. Problems endowments is a problem that until recently was less were discussed in intensive.The outline there is concentrate on the discussion problems fiqih, about the manner of philosophy Syari’ah, interest, finance and banking about the manner of Syari’ah and so on.While discussion from the his theory and application still very rare. From the penghimpunan community funds so it can be seen that discussion centered at issue zakat. While other sectors has not yet received the beam sufficient.And economic system islamic terdpat a lot of activity can be done to gather community funds.These funds could actually collected did not of funds zakat but also from a source – other sources as sadaqah, infaq, endowments and so on.